Environmental Cost Accounting Treatment and Their Effect on Financial Statements and Assessment of Sustainability Performance at PT Alove Bali - Luh Gede Nomica Eka Putri; I M Ariana; M Dana Saputra (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
This research aims to find out and analyze how PT Alove Bali identifies, acknowledges, measures, discloses and presents environmental costs and to determine the effect of environmental cost accounting treatment on financial statements as well as assessment of sustainability performance. This research focuses on analyzing primary data from interviews with 3 sources and observing the object of research as well as secondary data in the form of company financial statements as research supporting data. The analysis technique used is a qualitative descriptive analysis technique. This research provides results that the company has treated environmental cost accounting which consists of identification, recognition, measurement, disclosure and presentation even though the treatment is not fully in accordance with existing and supportive theories and standards. The company has recognized the cost of waste treatment even though it is still presented combined with other similar costs which are a component of production costs in the income statement. With this, the company has carried out environmental management properly so that the company has good sustainability performance for the future.